Kamper Aromatik Dari Limbah Parafin Dengan Penambahan Ekstrak Kulit Jeruk Nipis Untuk Alternatif Kamper Pabrikan - Ahmad Azis Rosyidi; Hinayuan Narendra, Hastu; Yahya, Ali; Handayani, Yuni (Jurnal Integrasi Sains dan Quran, 2023)
Abstract Camphor is a solid substance in the form of white paraffin with a distinctive and strong aroma. This substance is a terpenoid with the chemical formula C10H16O and contains naphthalene. Based on the Central Bureau of Statistics in 2021, total lime production in Indonesia will reach 797 tons. Demand for lime from year to year is also increasing. With the large production, the waste generated reaches 137 tons. This can cause environmental problems. The camphor used by the community contains terpenoids with the chemical formula C10H16O and naphthalene. According to the Louisiana State Department of Health, some of the chemicals in camphor such as naphthalene (C10H8) can cause health effects. Among these are headaches, nausea, eye and nose irritation, and coughing. Exposure to chemicals contained in camphor can cause more serious effects, namely hemolytic anemia. In response to this, this study aims to determine the process of making camphor from paraffin waste and lime peel extract to solve problems from lime peel waste and health problems from the effects of manufactured camphor. This study used a literature study for the content of paraffin waste as the main ingredient and lime peel as a substitute for the use of camphor. The research method used is descriptive quantitative. The test results obtained showed that the percentage of insect mortality from camphor products was greater than that from manufactured camphor, namely 8:7 and product camphor had a pH of 7.8 which complies with SNI 03-4147-1996 standards, which range from 7.5 to 9.5.